The occurrence of the preconditions for social exclusion in the Czech Republic: A basis for the planning of social prevention services - Eva Kovářová; Roman Vavrek (Review of Economic Perspectives, 2021)
Persisting social exclusion is one of the key issues the European Union Member States have to handle according to the headline targets of the Europe 2020 strategy. In the Czech Republic, more than 1 million people - 12.5% of the whole population - lived in the year 2019 at risk of poverty or social exclusion. Between the years 2010 and 2019, the monetary poverty rate oscillated around 10%. Although these are one of the lowest rates among the EU Member States, reduction and elimination of social exclusion has still been a challenge for the Czech policy-makers due to the relatively constant rates of monetary poverty, as low incomes are generally recognized as one of the causes of social exclusion. The aim of the paper is to identify the occurrence of the preconditions for social exclusion in the Czech districts revealed in the inter-district comparison that is based on the multi-criterial evaluation of the socio-economic situation in these districts. Such evaluation can serve as a basis for the planning of social prevention services, which are regarded as the means of prevention and reduction of social exclusion. Our findings obtained with the use of the Multi-Criteria Decision Making technique reveal that the occurrence of the preconditions for social exclusion varies among LAU1 districts of the Czech Republic and that districts lying in two NUT3 regions are affected more than others. Individuals living there are more likely to be socially excluded, especially if this higher probability derived from the districts' socio-economic situation is accompanied with their individual poor skills, health, or family breakdown.
Keywords: A13; C39; H55; 330; Coefficient of Variance; Multi-criteria analysis; Multiple disadvantage; Poverty; Social exclusion; Social services